(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Neurolinguistics is a field that looks at how our brain understands and uses language. When someone has a brain injury like a stroke it can damage the parts of the brain responsible for language. This can lead to problems with speaking, understanding, reading, or writing, a condition known as aphasia. In this article, we’ll look at how language works in the brain, how injuries can affect it, and how the brain can sometimes recover through something called neuroplasticity-its ability to adapt and rewire itself. We’ll also explore what current research and medical findings say about these topics.